THE INTELLECTUALIZATION OF PROCESS PHYSICAL CULTURE OF STUDENTS HIGH EDUCATION - Tatyana Evgenyevna Trufanova; Marina Vasilievna Katrenko; Aleksandr Aleksandrovich Prostyakov; Vladislav Olegovich Nazarov (Вестник Северо-Кавказского федерального университета)
As part of the basic components of physical culture of the individual incteasingly strong position takes its intellectual component. There is insufficient elaboration of the theoretical, methodological and organizational principles of formation of the intellectual component of physical education students personality. Key words: educational space, intellectualization component, education in the physical culture, creation of knowledge.